Jack Mezirow: Theorist, Researcher, Practitioner, Learner - Elizabeth Kasl (Adult Education Research Conference, 2015)
Jack Mezirow’s theory of adult learning is related to his beliefs about research and actualized in his vision for practice.
Keywords: Context; Epistemic Perspective; Practice